POST-OPERATIVE OF INTESTINAL OSTOMY: DIAGNOSIS AND NURSING INTERVENTIONS IMPLEMENTED IN CLINICAL PRACTICE (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: To identify nursing diagnoses and interventions implemented in clinical practice for patients in the postoperative period of intestinal ostomy based on the Theory of Basic Human Needs (NHB). Method: Quantitative, retrospective, and documentary study developed with 57 medical records of patients in the postoperative period of intestinal ostomy who were admitted to a general surgery unit of a hospital in the south of Brazil. Data were analyzed using descriptive statistics and grouped considering the NHB theory. Results: Twenty-five nursing diagnoses and 101 interventions were identified, which were mostly related to psychobiological NHB. The most frequent diagnoses were: Impaired tissue integrity (85.75%), and Risk of infection (26.25%). The nursing interventions checking vital signs (85.75%), and implementing colostomy/ileostomy care (80.5%) were characterized as the most prescribed ones. No diagnoses and interventions related to psychospiritual NHBs were obtained. Conclusion: The results revealed that nurses prioritized the psychobiological needs of patients, focusing care on the demands arising from the surgical intervention and its possible complications.